Ecosystem-based theoretical models for learning in environments of the 21st century - Gütl, C.; Chang, Vanessa (Online Journals, 2008)
Members of our modern society are faced with fast and ever-changing political, social, economical, technological and environmental situations. Consequently, it is expected that members of the society keep pace with these variable situations, and be able to adapt their skills and expertise. Thus, modern ICT-based learning approaches are required and E-Learning 2.0 is a promising and interesting approach in this context. Although there is an increasing interest in the E-learning 2.0 topic, there is a lack of concrete and sufficient models. In this paper we explore how the notion of ecosystems and existing ecosystem-based models for learning are applicable for E-Learning 2.0 approaches.